1976
DOI: 10.1056/nejm197603252941306
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Care of Low-Risk Mothers and Infants

Abstract: A family-centered perinatal-care program featuring collaboration by nurse practitioners, obstetricians, pediatricians, and paramedical personnel was developed to enhance family participation and achieve a shorter but safe hospital stay. Discharge from the hospital was permitted as early as 12 hours after delivery. A perinatal nurse practitioner made daily home visits. The program's safety, feasibility, and acceptability to patients was studied by comparison of 44 patients so treated (study group) with 44 recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
4

Year Published

1984
1984
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(48 citation statements)
references
References 8 publications
3
41
0
4
Order By: Relevance
“…Other studies have shown the safety of home-based follow-up after short maternity/nursery stays. 3,[63][64][65][66][67][68][69] Consistent with our group's previous retrospective study, 30 retrospective analyses of single HNVs have found benefits. Braveman et al 70 showed that acute care visits, rehospitalizations, and missed well-baby visits were less common among newborns who received a home nurse visit.…”
Section: Commentsupporting
confidence: 84%
“…Other studies have shown the safety of home-based follow-up after short maternity/nursery stays. 3,[63][64][65][66][67][68][69] Consistent with our group's previous retrospective study, 30 retrospective analyses of single HNVs have found benefits. Braveman et al 70 showed that acute care visits, rehospitalizations, and missed well-baby visits were less common among newborns who received a home nurse visit.…”
Section: Commentsupporting
confidence: 84%
“…In almost all programs, these home follow-up services were provided by nurses with advanced training, from baccalaureate preparation with physical assessment skills (6) to nurse-practitioners and certified nurse-midwives, family nurse-practitioners, or perinatal nurse practitioners (1,5, 8,9). Only one program did not regularly use nurses to provide early discharge follow-up (7).…”
Section: Program Populations and Proceduresmentioning
confidence: 99%
“…[18][19][20][21] The hypothesis of this study is that shorter postpartum stays are associated with poor health outcomes because of the decreased probability of detecting postpartum complications, as has been found in studies with other populations. 22 Little information is available in Mexico to assess the potentially negative effects of early hospital discharge on maternal health during early puerperium, defined as the period between 24 hours to 7 days postpartum.…”
Section: Introductionmentioning
confidence: 99%